2010
DOI: 10.1016/j.otsr.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Proximal tibial derotation osteotomy for torsional tibial deformities generating patello-femoral disorders

Abstract: level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 13 publications
0
50
0
Order By: Relevance
“…This, however, could be important information when planning a derotational osteotomy. Currently, debate still surrounds the ideal site for an osteotomy, which can be performed proximally or distally [4,8,9,21,22]. If an osteotomy is performed at the site of the deformity, normal anatomy can be restored [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, however, could be important information when planning a derotational osteotomy. Currently, debate still surrounds the ideal site for an osteotomy, which can be performed proximally or distally [4,8,9,21,22]. If an osteotomy is performed at the site of the deformity, normal anatomy can be restored [6].…”
Section: Discussionmentioning
confidence: 99%
“…While the treatment of deformities in frontal or sagittal plane is based on well-established rules drawing on the concept of the centre of rotation of angulation (CORA) [6,7], there are no specific treatment rules for femoral torsional deformities. Hence, disagreement still prevails on whether an osteotomy should be performed proximally or distally in patients with pathologic femoral torsion [8,9]. Knowing the segment of the femur in which a torsional deformity is actually localized (i.e., concept of CORA) could help us in this discussion and eventually improve treatment guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…32 The relationship between these factors is complex, with both dynamic and static forces acting on the patella in all three cardinal planes. While proximal alignment (e.g., Q-angle, 40, 41 femoral rotation 16, 43 ) and muscle imbalances (e.g., vasti medialis-lateralis weakness, 37, 50 altered EMG timing between the vastus medialis and lateralis 9, 49 ) have been extensively studied in cohorts with PFP, the potential contribution of lateralization of the patellar tendon in this population has not been evaluated in a large cohort of individuals with isolated PFP..…”
Section: Introductionmentioning
confidence: 99%
“…Yet, TT osteotomy has been performed in patients with isolated PFP without a clear understanding that the direction of pull on the patella from the patellar tendon is a likely contributing factor to PFP. 4, 16, 17, 19, 24, 34, 47 …”
Section: Introductionmentioning
confidence: 99%
“…Fouilleron et al reported on a technique to correct both varus and rotation but did not compare this to varus correction alone. 8 Some of the effects of external tibial torsion have been elucidated 9,10 but more likely exist. It is plausible that the correction of genu varum without addressing tibial torsion will lead to an inferior outcome.…”
mentioning
confidence: 99%